Endoscopic ultrasound-directed transgastric ERCP (EDGE): a systematic review describing the outcomes, adverse events, and knowledge gaps - Prakash, Shaurya; Elmunzer, B. Joseph; Forster, Erin M.; Cote, Gregory A.; Moran, Robert A. (Endoscopy, 2021)
Background Endoscopic ultrasound-directed transgastric endoscopic retrograde cholangiopancreatography (EDGE) has emerged as a viable completely endoscopic method for performing pancreaticobiliary interventions in patients with Roux-en-Y gastric bypass anatomy. The aims of this systematic review were: (1) to describe the indications, outcomes, and complications of EDGE; and (2) to identify deficiencies in our knowledge of important technical approaches and clinical outcomes.Methods A systematic review was conducted via comprehensive searches of Medline, Scopus, CINAHL, and Cochrane to identify studies focusing on EDGE outcomes. Simple descriptive statistics were derived from case series only. Case reports were only included to qualitatively describe additional indications, techniques, and adverse events.Results The initial search identified 2143 abstracts. Nine case series and eight case reports were included. In the nine case series, 169 patients underwent EDGE. The technical success rate was 99 % (168 /169) for gastrogastrostomy/jejunogastrostomy creation and 98 % (166 /169) for subsequent ERCP. Minor adverse events specifically related to EDGE occurred in 18 % (31/169) and included intraprocedural stent migration/malposition (n = 27) and abdominal pain (n = 4). Moderate adverse events specific to EDGE occurred in 5 % (9/169): including bleeding (2 %), persistent fistula (1 %), and perforation (1 %). Severe adverse events occurred in one patient with a perforation requiring surgery. Deficiency in reporting on the clinical significance of adverse events was identified.Conclusion Based on limited observational data, in expert hands, EDGE has a high rate of technical success and an acceptable rate of adverse events. As a novel procedure, many knowledge gaps need to be addressed to inform the design of meaningful comparative studies and guide informed consent.